Assessing the implementation of the electronic salary payment voucher of the controller and accountant general department: a case study of Ghana education service (GES) - Asombala, Rita (KNUST, 2025)
A thesis submitted to the Department of Human Resource and Organizational Development, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement for the degree of Master of Business Administration (H R M Option) School of Business, KNUST College of Humanities and Social Sciences